(untitled) (El Hilo de la Fabula, 2018)
Focusing on the notion of «novísima poesía» —the newest poetry— developed by Edgardo Antonio Vigo, this article analyses relationships between digital and experimental poetry. Even if Vigo never wrote digital poetry, the kind of poetics promoted by him can be easily intertwine with digital poetry experimentation. Argumentation is based on the potentiality of experimental poetry digital, articulated whit the kind of poetics Vigo encouraged, to opening artistic experience towards new forms of life, surpassing standardized paths within informational societies and in opposition to its mere novelty.